Educational and Career-related Help-seeking in High School: An Exploration of Students’ Choices - Domene, José F.; Shapka, Jennifer D.; Keating, Daniel P. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study examined patterns of help-seeking for educational and career planning issues in a sample of 483 students in grades 11–12 from two schools in southern Ontario. Although counsellors were the most common source of support for educational issues, very few students sought their assistance for career issues, choosing to turn to family members instead. Logistic regression revealed that males and students with lower occupational aspirations were more likely to avoid seeking assistance from counsellors for educational planning issues, while males, students with lower educational aspirations, and students with parents who attained higher levels of education were least likely to see counsellors for career planning. These results indicate that it is important to more fully explore student, counsellor, and contextual infl uences on help-seeking in the career domain, in order to design alternative intervention strategies for individuals who do not seek assistance from their school counsellors.